Gambaran Status Gizi Balita di Wilayah Kerja Puskesmas Semitau - Tika Tika; Selasih Putri Isnawati; Eka Vicky Yulivantina (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2026)
Nutritional problems among children under five remain a public health concern in Indonesia, including in the working area of Semitau Public Health Center, Kapuas Hulu Regency. Nutritional status is an important indicator in assessing child growth and development. Nutritional disorders such as undernutrition, severe undernutrition, and stunting may have long-term impacts on health, cognitive development, and productivity. Therefore, regular monitoring of nutritional status is necessary to determine the nutritional profile of children under five in the Semitau Public Health Center area. Objective: This study aimed to describe the nutritional status of children under five based on Weight-for-Age (W/A), Height-for-Age (H/A), and Weight-for-Height (W/H) indicators, as well as to describe the characteristics of mothers and children. Methods: This study used a descriptive method with a retrospective approach. Data were obtained from the recap of child weighing results in March 2025 in the working area of Semitau Public Health Center. The study population consisted of 395 children aged 0–59 months, with 351 children meeting the inclusion criteria selected using total sampling technique. Data were analyzed univariately to obtain the frequency distribution of nutritional status. Results: Based on W/A, 77% of children had normal nutritional status, 13.5% were undernourished, 6.1% were severely undernourished, and 1.0% were overweight. Based on H/A, 62.1% were normal, 20.8% were stunted, 11.5% were severely stunted, and 1.8% were tall. Based on W/H, 76.4% had normal nutritional status, 7.9% were undernourished, 2.0% were severely undernourished, 3.1% were overweight, and 2.6% were obese. Conclusion: The majority of children under five in the Semitau Public Health Center area had normal nutritional status. However, the stunting prevalence of 32.3% remains high according to WHO classification. Strengthening nutritional monitoring through integrated health posts and providing parental education on balanced nutrition are recommended.